LEPTOSPIROSIS CASE FINDING FOR DEVELOPMENT OF LEPTOSPIROSIS SURVEILLANCE IN SEMARANG CITY, CENTRAL JAVA, INDONESIA - Ristiyanto Ristiyanto; Farida Dwi Handayani; Arief Mulyono; Arum Sih Joharina; Tri Wibawa; Setyawan Budiharta; Supargiono Supargiono (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Leptospirosis is primarily a disease of wild and domestic animals, and may be transmitted to humans through direct or indirect contact with infected animal urine. Leptospirosis is endemic in part of Indonesia territory. This work aimed to find the leptospirosis cases in Semarang city, one of the endemic leptospirosis in Indonesia by active and passive case finding. The leptospirosis were screened in the community base active case finding and passive case finding in primary health care center and hospitals, by using modified WHO-SEARO criteria and laboratory confirmation test. There were 191 cases detected with modified WHO-SEARO criteria, and among those cases only 31 cases confirmed by laboratory test, either by using Rapid Detection Test (RDT), Microscopic Agglutinations Test (MAT) or Polymerase chained reaction (PCR). It was found that leptospirosis was not correlated with rainfall season. Fever, headache and myalgia were the most common symptoms experienced by >90% patients. Active case finding add no more than 7% probable leptospirosis and 14% confirmed cases to the traditional passive case finding. It was conclude that leptospirosis case finding is still challenging in the endemic area, such as Semarang city. The application of modified WHO-SEARO criteria as diagnostic tool may be needed to be further evaluated. Keywords: Leptospirosis, Surveillance, Case finding, Endemic, Detection